SIP1/NHERF2 enhances estrogen receptor alpha transactivation in breast cancer cells - Meneses-Morales, Ivan (Oxford University Press, 2014)
The estrogen receptor alpha (ERα) is a ligand-activated transcription factor that possesses two activating domains designated AF-1 and AF-2 that mediate its transcriptional activity. The role of AF-2 is to recruit coregulator protein complexes capable of modifying chromatin condensation status. In contrast, the mechanism responsible for the ligand-independent AF-1 activity and for its synergistic functional interaction with AF-2 is unclear. In this study, we have identified the protein Na+/H+ Exchanger RegulatoryFactor 2 (NHERF2) as an ERα-associated coactivator that interacts predominantly with the AF-1 domain of the nuclear receptor. Overexpression of NHERF2 in breast cancer MCF7 cells produced an increase in ERα transactivation. Interestingly, the presence of SRC-1 in NHERF2 stably overexpressing MCF7 cells produced a synergistic increase in ERα activity. We show further that NHERF2 interacts with ERα and SRC-1 in the promoter region of ERα target genes. The binding of NHERF2 to ERα in MCF7 cells increased cell proliferation and the ability of MCF7 cells to form tumors in a mouse model. We analyzed the expression of NHERF2 in breast cancer tumors finding a 2- to 17-fold increase in its mRNA levels in 50% of the tumor samples compared to normal breast tissue. These results indicate that NHERF2 is a coactivator of ERα that may participate in the development of estrogen-dependent breast cancer tumors.